Vanishing acts - Margolin, Phillip (Margolin, Phillip. Madison Kincaid mystery., 2011)
In Portland, Oregon, between soccer games and beginning seventh grade, twelve-year-old Madison Kincaid and new classmate Jake try to track down her missing best friend, while also helping her attorney father solve a missing-persons case.